Médiations autour du patrimoine de l’esclavage à l’Écomusée municipal d’Approuague-Kaw (Guyane) : enjeux, état des lieux et perspectives - Damien Hanriot (In Situ)
The community eco-museum, Écomusée municipal d’Approuague-Kaw (Régina, French Guiana), is a Museum of a vast territory. It recently focused on the colonial and slavery period of the Lower-Approuague where the artifacts and features of this forgotten past can still be found today. The Museum and its partners developed a research program on plantation sites that all present polders built by the slaves just before the French Revolution in 1789 and industrial structures introduced in Guiana between 1820-1830 (in particular the emblematic Watt steam engine). The area is a true out-door museum. Visitors can explore the archaeological remains of an ancient sugar plantation, in the amazonian forest. The interpretation of the heritage which is proposed evolves according to the archaeological and historic research. Due to the ongoing scientific research in the field, the visitor plays an active role in the conservation, the restoration and the development of this local heritage. What can we or what do we have to restore? What are the problems faced by conservation? Which interventions are needed ? The local history of slavery is at the center of educative, cultural and memorial issues.